Development of a criticality scale related to hoaxes in social media - Dharmastuti, Anjarie; Wiyono , Bambang Budi; Hitipeuw, Imanuel; Rahmawati, Hetti; Wahyuni, Fitri; Apriliyanti , Fressi (Bulletin of Social Informatics Theory and Application, 2021)
The massive circulation of hoaxes on social media is currently a fairly complex problem in society. One simple way that is considered effective to reduce the rate of hoaxes is to not disseminate information without prior verification. Verification efforts with the aim of minimizing the impact of this hoax can be referred to as criticality. The term criticality is basically still quite new when compared to the term critical thinking. Criticality refers to the concept of critical thinking accompanied by a commitment to act based on socio-cultural values. The purpose of this study was to develop a criticality scale related to hoaxes on social media. The method used is quantitative involving 400 students from state universities in Malang City. The results of this study indicate that the criticality scale related to hoaxes developed has met the criteria of good validity and reliability.